Towards ab Initio Thermodynamics of the Electron Gas at Strong Degeneracy. Issue 2 (4th December 2014) - Schoof, T.; Groth, S.; Bonitz, M.
Abstract: Recently a number of theoretical studies of the uniform electron gas (UEG) at finite temperature have appeared that are of relevance for dense plasmas, warm dense matter and laser excited solids and thermodynamic density functional theory simulations. In particular, restricted path integral Monte Carlo (RPIMC) results became available which, however, due to the Fermion sign problem, are confined to moderate quantum degeneracy, i.e. low to moderate densities. We have recently developed an alternative approach–configuration PIMC [T. Schoof et al., Contrib. Plasma Phys.51, 687 (2011)] that allows one to study the so far not accessible high degeneracy regime. Here we present the first step towards UEG simulations using CPIMC by studying implementation and performance of the method for the model case of N = 4 particles. We also provide benchmark data for the total energy. (© 2015 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)